Optimization of Chicken Satay Culinary Business Based on Local Wisdom: Empirical Study of Gang Sate Jalan Lawu Ponorogo - Wulandari, Ririn; Hutabarat, Ruth Eviana (CV. Ulil Albab Corp, 2025)
Indonesia has abundant resource potential, but still faces problems of poverty and unemployment. MSMEs, particularly the culinary sector, play an important role in economic development with their contribution to employment and GDP. Local wisdom-based culinary, such as Ponorogo Chicken Satay, has great potential to increase community income and preserve regional culture. This study focuses on the optimization of the Chicken Satay culinary business in Gang Sate Jalan Lawu Ponorogo. The aim is to analyze the potential, challenges, and development strategies of local wisdom-based businesses to support the improvement of community welfare and regional economic growth. This research analyzes the potential and development strategies of the Ponorogo Chicken Satay business at Gang Sate Jalan Lawu, Ponorogo. The method used is descriptive qualitative with an empirical approach. Data were obtained through observation, structured interviews, and documentation from satay producers. A purposive sampling technique was used to select informants. The results showed that the Ponorogo Chicken Satay business plays an important role in the local economy and preservation of regional culture.